2011
DOI: 10.1007/s10875-011-9631-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher Doses of Subcutaneous IgG Reduce Resource Utilization in Patients with Primary Immunodeficiency

Abstract: The recommended dose of IgG in primary immunodeficiency (PID) has been increasing since its first use. This study aimed to determine if higher subcutaneous IgG doses resulted in improved patient outcomes by comparing results from two parallel clinical studies with similar design. One patient cohort received subcutaneous IgG doses that were 1.5 times higher than their previous intravenous doses (mean 213 mg/kg/week), whereas the other cohort received doses identical to previous subcutaneous or intravenous doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…8,189,190 Higher rates of respiratory infection and poorer outcomes are associated with underdosing IgG and vice versa. 50,191,192 …”
Section: Managementmentioning
confidence: 99%
“…8,189,190 Higher rates of respiratory infection and poorer outcomes are associated with underdosing IgG and vice versa. 50,191,192 …”
Section: Managementmentioning
confidence: 99%
“…A study by Haddad et al 51 in pid showed that higher doses of scig (mean: 213 mg/kg vs. 120 mg/kg weekly) resulted in lower rates of nonserious infections (2.76 episodes vs. (Table iii) 52,53 . A study evaluating the cost savings of scig in a Canadian setting found the net economic gain from switching 1 patient with pid or secondary immunodeficiency disorder to home-based scig care to be $2,603 in the first year and $2,948 in each subsequent year 54 .…”
Section: Cost-effectiveness Of Ig Therapymentioning
confidence: 99%
“…The number of other infections was found to be lower when the coefficient was used (21). On the other hand, the characteristic of protection from infection was also a valid principle for administration of IVIG when the IgG replacement dose was increased (22).…”
Section: Discussionmentioning
confidence: 96%